1990
DOI: 10.1016/s0022-5347(17)39746-x
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Peyronie’s Disease

Abstract: The natural history of Peyronie's disease was evaluated in 97 men by means of a questionnaire. Disease duration ranged from 3 months to 8 years. Questions addressed pain, bending, ability for intercourse, over-all effect of the disease, psychological effects, treatments received and degree of disease progression. Approximately 40% of the patients found pain, bending, ability for intercourse and over-all effects to be unchanged during the course of the disease. Bending and ability for relations worsened in 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
259
4
32

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(301 citation statements)
references
References 5 publications
6
259
4
32
Order By: Relevance
“…30 suggesting that nonvascular factors may be responsible for the occurrence of ED in patients with PD. Such factors may include pain 10,21 and other comorbid conditions (eg, hypercholesterolemia), 8 which are prevalent among patients with PD. However, in a retrospective study of men with complaints of penile curvature and shortening who underwent penile duplex Doppler ultrasonography, demographic and baseline disease characteristics (eg, age, diabetes, smoking, hyperlipidemia, hypertension) were similar in patients with PD alone and in those with PD and ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 suggesting that nonvascular factors may be responsible for the occurrence of ED in patients with PD. Such factors may include pain 10,21 and other comorbid conditions (eg, hypercholesterolemia), 8 which are prevalent among patients with PD. However, in a retrospective study of men with complaints of penile curvature and shortening who underwent penile duplex Doppler ultrasonography, demographic and baseline disease characteristics (eg, age, diabetes, smoking, hyperlipidemia, hypertension) were similar in patients with PD alone and in those with PD and ED.…”
Section: Discussionmentioning
confidence: 99%
“…Factors underlying this connection remain unknown, 13 but both conditions have been associated with increased age, 2,14-16 comorbid disorders (eg, diabetes, 2,8,16 cardiovascular events, 17,18 radical prostatectomy 19,20 ), psychological symptoms, [9][10][11]15,21,22 and altered blood flow. 13 In addition, ED has been associated with depression, 22 which, similar to PD, may influence a patient's assessment of physical and psychological functioning.…”
mentioning
confidence: 99%
“…Patients had received two or more previous treatments for PD, including potassium aminobenzoate, tamoxifen, colchicine, systemic steroids and intralesional verapamil. Gelbard et al 12 compared vitamin E therapy to the natural history of PD in 97 patients with disease duration ranging from 3 months to 8 years; no significant differences were found between the two groups in terms of curvature, pain or the ability to have intercourse. To date, no placebo-controlled trials using vitamin E have demonstrated any clinical benefit in the treatment of PD, and there is some evidence that vitamin E may also increase the risk of cerebrovascular events.…”
Section: Carnitinementioning
confidence: 99%
“…This group of investigators previously reported that 48% of patients had curvature progression in a no-treatment natural history observation study. 47 The first randomized, single-blind trial of intralesional verapamil was published in 1998 by Rehman et al 48 Significant improvements were noted in terms of erection [6][7][8][9][10][11][12][13][14][15][16][17][18], and all patients were treatmentnaive before entry into the study. Curvature was measured during duplex ultrasound of a pharmacologically induced erection.…”
Section: Intralesional Therapiesmentioning
confidence: 99%
See 1 more Smart Citation